Assessment of Public Relations Strategies Employed by UNICEF in Management of IDP Camps in Maiduguri, Borno State - Madu, Bwala Winifred; Kente, Josiah Sabo; Akase, T. M. (EDUMALSYS Journal of Research in Education Management, 2025)
This study investigated public relations strategies employed by UNICEF in the management of Internally Displaced Persons (IDP) camps in Maiduguri, Borno State, with the objective of assessing their relevance and effectiveness in addressing humanitarian challenges. Guided by Structural Theory and Stakeholder Theory, the research adopted a survey design and utilized questionnaires administered to a sample of 400 respondents drawn from a projected population of 4,143,100, as estimated by the National Bureau of Statistics for 2024. The findings indicate that UNICEF primarily relied on religious and community leaders to drive campaigns, followed by the use of social media messages, public events, financial aid distribution, sponsored campaigns, press releases, and press conferences. Among these, the engagement of religious and community leaders emerged as the most effective strategy. Nevertheless, the study highlights persistent challenges in implementing public relations approaches, particularly limited cooperation and support from government authorities. The study concludes that sustained government support in terms of resources and logistics is essential for effective public relations interventions. It further recommends the continued involvement of religious and community leaders as campaign mediators, complemented by capacity-building initiatives such as crisis communication training to enhance the quality of service delivery.